Synthesis, characterization and electrochemical properties of O-alkyldithiophosphate nickel complexes with dppf ligand. (15th February 2018) - Ma, Xiao; Xie, Bin; Li, Yulong; Deng, Chenglong; Feng, Jianshen; Wei, Jian; Lai, Chuan; Zou, Like; Wu, Yu; Wang, Jun; He, Linxin; Zhang, Dongliang
Graphical abstract: Four novel O-alkyldithiophosphate nickel complexes [(dppf)Ni(S2 POOR)] have been synthesized and structurally characterized. The coordination geometry around the nickel atom is slightly distorted from square-planar configuration in their crystals. All the four complexes can electrocatalyze proton reduction to hydrogen in the presence of trifluoroacetic acid and acetic acid in CH2 Cl2 solution, respectively. Abstract: Four new O-alkyldithiophosphate nickel complexes [(dppf)Ni(S2 POOR)] with dppf ligand (1, R = CH3 ;2, R = CH2 CH3 ;3, R = CH2 Ph;4, R = CH2 CH2 Ph; dppf = 1, 1′-bis(diphenylphosphino)ferrocene) have been synthesized by treatment of (dppf)NiCl2 with (RO)2 PS2 NH2 Et2 in good yields. All the four complexes were characterized by elemental analysis, spectroscopy (IR, UV–Vis, 1 H, 13 C and 31 P NMR), thermogravimetric analysis and single crystal X-ray diffraction. The crystal structures of1 –4 reveal that the nickel atom lies at the center of a slightly distorted square-planar environment and all complexes display CH⋯Ni intramolecular anagostic interactions. Furthermore, the electrochemical properties for1 –4 were also investigated by cyclic voltammetry. The electrochemical studies indicate that all complexes can be used as eletrocatalysts for reduction proton to hydrogen in the presence of trifluoroacetic acid and acetic acid in CH2 Cl2 solution, respectively.